Network dynamics of human face perception: the salience of infant faces and implications for caregiving - Stark, E (2020)
This thesis provides novel neuroimaging insights into the brain activity related to the processing of highly salient infant faces. Specifically, I provide new information about the spatial and temporal aspects of brain activity for processing infant faces within four experimental investigations. Overall, the presented findings provide novel, important insights into: (1) our current understanding of how the brain processes salient, infant faces, (2) human face perception more generally, and (3) potential implications for how we provide care to our young.